Characterization of an asymmetric add‐on collimator used with a hand‐held gamma probe for radioguided surgery and sentinel node detection: a demonstration of an alternative collimation method. (12th June 2013) - Johnsrud, Kjersti; Skretting, Arne; Naum, Alexandru G.; Bogsrud, Trond V.; Bach‐Gansmo, Tore
Summary: Objective: The aim of the study was to investigate a new principle for collimation of gamma probes for radioguided surgery and sentinel node detection: the use of asymmetric lateral shielding. The intension was to maintain the sensitivity in the lateral and forward directions on the unshielded side while at the same time to shield the probe against high activity sources that could mask the signal from the object to be detected. Methods: The device was constructed to shield only against photons that come from a region in space that spans approximately 180° sideways and forwards relative to the detector. The intension of the study was to demonstrate the principle rather than to document its use in the clinic. Sensitivity profiles were derived from measurements obtained while stepwise moving the probe relatively to a point source of known activity surrounded by water. The measurements were taken in the symmetry plane of the collimator where the shielding effects were expected to be most pronounced. Results: The asymmetric collimator led to nearly unchanged sensitivity in the lateral and forward directions. At the same time, the field of view was effectively shrunk on the shielded side. Contributions from sources lateral and close to the shield were reduced by factors up to 45. Conclusion: By rotating the probe around its longitudinal axis, an asymmetric add‐on shield collimator could potentially make it easier to detect a sentinel node when this is located close to a neighbouring high activity region like the urinary bladder or the injection site.